TEKNIK BUDIDAYA HIDROPONIK DENGAN SISTEM RAKIT APUNG DI DESA HARAPAN JAYA, PELALAWAN - Intan Kartika Sari; Ade Irma Rosida; Siti Sephia; Yulia Syafitri; Riski Prakoso; Nia Omega; Yohana Febriyanti; Sofia Kristin; William Gerald; Yedija Triyanta Sy; Michael Josua (Nusantara Hasana Journal, 2022)
Community service activities were carried out in Harapan Jaya Village, Palalawan Regency with the aim of providing information to the public about plant cultivation systems with a simple hydroponic system. This outreach activity was motivated by the less than optimal use of yard land and the low level of public knowledge about vegetable cultivation techniques with modern hydroponic systems. This is because there has been no socialization about hydroponics in Harapan Jaya Village. Hydroponics is an alternative that can be used to increase the availability of healthy and quality vegetables in a limited area. Based on several types of hydroponic systems that can be done, hydroponics with a floating raft system is one system that is quite simple and easy to apply on a residential scale. Extension activities are carried out through three processes, namely the provision of material, question and answer sessions and practical demonstrations. The result of this activity is that residents better understand how to grow hydroponically in limited land use and residents get simple hydroponic packages that can be practiced at home.